Pengaturan, Penanganan dan Pertanggungjawaban Hukum Bagi Pelaku Tindak Pidana Pembayaran Melalui Cek Giro Kosong - Mahzaniar Mahzaniar (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2017)
Implementation of payment through blank checks is one of the modern modus operandi of crime today. Payments through blank checks can be classified and put into crime fraud. The legal arrangements for the criminal acts of payment through blank checks are stipulated in Article 378 of the Criminal Code. This means that the criminal act of payment through blank check is entered into the classification of fraud criminal acts as stipulated in Article 378 of the Criminal Code. The party involved in handling the crime of payment through blank check is the police. Because the function of the police is one of the functions of state government in the field of maintaining security and public order, law enforcement, protection, penganyoman, and service to the community. The legal liability for the perpetrator of a criminal act of payment through the blank check is punished for the act. If the act of intimidation is done intentionally, then done consciously by a sane person and known the act of fraud there is regulated in the legislation that is Article 378 of the Criminal Code, so in this capacity the perpetrators of fraud can be held accountable law.